The factors affecting retirement planning behavior: the case of Selangor and Negeri Sembilan / Nur Zarinah Nordin and Nurul Afiqah Sudirman - Nordin, Nur Zarinah; Sudirman, Nurul Afiqah (Faculty of Business and Management, 2014)
Awareness in retirement planning in Malaysia still becomes an important issue in Malaysia. There are a lot of retirement scheme and also step for retirement saving being introduced by financial institutions. Nevertheless, many studies have shown that money saved in companies and government pension plan may not be adequate for future consumption. Therefore, this project paper aimed at discussion demographic factors, financial education background, work-related variables and goal clarity factors towards retirement planning behavior among individual workers in Malaysia. As a result, a theoretical framework is developed to illustrate the relationship between demographic, financial education background, work-related variables and goal clarity with retirement planning.